IMPACT OF URBANIZATION ON SOCIAL STRUCTURES: A CASE STUDY OF ROHTAK DISTRICT - Kumar, Raj (International Journal of Engineering Technologies and Management Research, 2025)
Urbanization has significantly transformed social structures across the globe, influencing various aspects of life such as family dynamics, community interactions, economic participation, and cultural practices. This study explores the impact of urbanization on the social fabric of Rohtak district, Haryana, with a focus on changes in societal norms, mobility, and social hierarchies. Using a mixed-methods approach, this paper analyzes demographic trends, shifts in employment patterns, and alterations in family structures and social interactions due to urban expansion. The research finds that urbanization in Rohtak has led to increased migration, particularly among youth, which has affected traditional family systems, and has contributed to the rise of individualism while challenging collective cultural practices. Additionally, the study highlights the role of infrastructure development and access to education in reshaping social inequalities, with urban areas exhibiting greater socio-economic mobility compared to rural regions. The findings provide insights into the broader implications of urban growth on local social systems, contributing to discussions on sustainable urban planning and its social consequences.